Menanamkan Toleransi Multi Agama sebagai Payung Anti Radikalisme: Studi Kasus Komunitas Lintas Agama dan Kepercayaan di Pantura Tali Akrab - Mutiara, Kholidia Efining (FIKRAH, 2016)
This article specifically aims at describing Indonesia as one of the multi-religious country having a lot of various confidence and trust, but from the religious differences is able to bring about actions of radicalism. Therefore, tolerance maintenances need to emphasize to every individual, as we have already applied to the interfaith community of PANTURA. This study used a case study approach in inter-religious and belief communities of PANTURA, known as TALI AKRAB, which is one of the various religious friendship communities in the northern coasts (PANTURA) of Indonesia. The main findings in this paper include the way of instilling a multi-religious tolerance as a tool of avoiding radicalism in society, by discussing the problems of each religion and ignoring differences in the faith.